Two algebraic equations are given and each equation is in terms of $a$ and $b$. The value of $a$ and $b$ are required to find by solving them in this problem.

$ {(\sqrt{243})}^{\displaystyle \, a} \div 3^{\displaystyle \, b+1} = 1$

$27^{\displaystyle \,b} -81^{\displaystyle 4-\frac{a}{2}} = 0$

01

Firstly, let us simplify the first given equation.

$ {(\sqrt{243})}^{\displaystyle \, a} \div 3^{\displaystyle \, b+1} \,=\, 1$

$\implies$ $ \dfrac{{\Big(\sqrt{243}\Big)}^{\displaystyle \, a} }{ 3^{\displaystyle \, b+1} } \,=\, 1$

The base of exponential term in denominator is $3$. So, express the $243$ as an exponential term on the basis of number $3$.

$\implies$ $ \dfrac{{\Big(\sqrt{3^5}\Big)}^{\displaystyle \, a} }{ 3^{\displaystyle \, b+1} } \,=\, 1$

The symbol of the square root ($\sqrt{\,\,\,}$) represents the exponent $\dfrac{1}{2}$.

$\implies$ $ \dfrac{{\Big({\Big[3^5\Big]}^\frac{1}{2} \Big)}^{\displaystyle \, a} }{ 3^{\displaystyle \, b+1} } \,=\, 1$

Use power rule of exponent of an exponential term and simplify the numerator.

$\implies$ $ \dfrac{{\Big(3^\frac{5}{2}\Big)}^{\displaystyle \, a} }{ 3^{\displaystyle \, b+1} } \,=\, 1$

$\implies$ $\dfrac{3^\frac{5a}{2}}{3^{\displaystyle \, b+1}} \,=\, 1$

Cross multiply the denominator to shift it to right hand side of the equation.

$\implies$ $3^\dfrac{5a}{2} \,=\, 3^{\displaystyle \, b+1}$

$\implies$ $\dfrac{5a}{2} \,=\, b+1$

$\therefore \,\,\,\,\,\,$ $5a \,=\, 2(b+1)$

02

Now, consider the second equation to simplify it.

$27^{\displaystyle \,b} -81^{\displaystyle 4-\frac{a}{2}} = 0$

$\implies$ $27^{\displaystyle \,b} \,=\, 81^{\displaystyle 4-\frac{a}{2}}$

Write the numbers $27$ and $81$ in exponential notation on the basis of number $3$.

$\implies$ ${(3^3)}^{\displaystyle \,b} \,=\, {(3^4)}^{\displaystyle 4-\frac{a}{2}}$

Apply the power rule of power of an exponential term to simplify the equation further.

$\implies$ $3^{\displaystyle \,3b} \,=\, 3^{\displaystyle 4\Big(4-\frac{a}{2}\Big)}$

The bases of the both exponential terms are same. So, the exponents should be equal mathematically.

$\therefore \,\,\,\,\,\,$ $3b \,=\, 4\Big(4-\dfrac{a}{2}\Big)$

03

Now, consider the simplified equations and try to solve them to obtain the value of $a$ and $b$.

$5a = 2(b+1)$

$3b \,=\, 4\Big(4-\dfrac{a}{2}\Big)$

There is a $\dfrac{a}{2}$ term in the second equation, the first equation can be expressed as $\dfrac{a}{2}$ to substitute its value in the second equation. So, transform the first equation as follows.

$\implies$ $\dfrac{a}{2} = \dfrac{b+1}{5}$

Now, substitute it in the second equation.

$\implies$ $3b \,=\, 4\Big(4-\dfrac{b+1}{5}\Big)$

$\implies$ $3b \,=\, 4\Big(\dfrac{20-b-1}{5}\Big)$

$\implies$ $3b \,=\, 4\Big(\dfrac{19-b}{5}\Big)$

$\implies$ $5 \times 3b \,=\, 4\Big(19-b\Big)$

$\implies$ $15b \,=\, 76-4b$

$\implies$ $15b+4b \,=\, 76$

$\implies$ $19b \,=\, 76$

$\implies$ $b \,=\, \dfrac{76}{19}$

$\implies$ $\require{cancel} b \,=\, \dfrac{\cancel{76}}{\cancel{19}}$

$\therefore \,\,\,\,\,\,$ $b \,=\, 4$

Now, substitute the value of $b$ in any equation for getting the value of $a$. Here, the first equation is considered.

$5a = 2(4+1)$

$\implies$ $5a = 2 \times 5$

$\implies$ $\require{cancel} \cancel{5}a = 2 \times \cancel{5}$

$\therefore \,\,\,\,\,\,$ $a = 2$

Latest Math Topics

Latest Math Problems

Email subscription

Learn how to solve easy to difficult mathematics problems of all topics in various methods with step by step process and also maths questions for practising.